Corneal epithelial thickness profile at different corneal zones of normal eyes in a population sample from northern Iran: A cross-sectional study - Reza Soltani Moghadam; Mitra Akbari; Parisa Rouhani; Abdolreza Medghalchi; Ehsan Kazemnezhad Leili; Ebrahim Azaripour (Oman Journal of Ophthalmology, 2025)
BACKGROUND: Determination of the normal range of corneal epithelial thickness (CET) profiles in different populations is important. Accordingly, the present study aimed to investigate the CET in normal eyes in Guilan province of Iran. MATERIALS AND METHODS: In this cross-sectional study, a total of 169 patients (18–60 years old) who were referred to the ophthalmology clinics in Rasht for corneal refractive surgery were included. They underwent a complete ophthalmological examination, including visual acuity, intraocular pressure examination, and fundoscopy examination with a 90 D lens. Spectral-domain optical coherence tomography was used to examine CET; corneal epithelial mapping was done with Optovue I scan 500s. RESULTS: The mean CET at 5–6 mm and 2–5 mm zones was 52.88 ± 2.8 and 53.24 ± 2.9, in the 2 mm of the center was 53.67 ± 3.24, in the superior and inferior 5–6 mm zone was 50.8 ± 3.18 and 54.38 ± 3.53, and in superior and inferior 2–5 mm zone was 52.14 ± 2.98 and 54.41 ± 3.60, respectively; there was a significant difference between 5–6 and 2–5 mm of the superior zone. The supratemporal region had the thinnest epithelium, and the inferior region had the thickest. The central CET was statistically different between males and females, and the relationship between paracentral and peripheral thickness (2–5 and 5–6 mm) with age, especially in ages 33–46 and 47–60, was stronger. CONCLUSION: The values of the CET map, defined in the present study, in a sample of Guilan population with normal eyes, can be further used as a reference (normal) range for this population.